Frequency-amplitude correlation inducing first-order phase transition in coupled oscillators. (1st July 2022) - Wang, Jiangsheng; Gu, Changgui; Ji, Peng
Abstract: The first-order phase transitions in coupled oscillators have been widely studied because of their discontinuity and irreversibility. In previous research, the designed coupling mechanisms between each pair of oscillators can cause the first-order phase transitions occur stably. In the present study, we propose a new mechanism which requires the existence of an inversely proportional relationship between the natural frequencies and the intrinsic amplitudes in the homogeneously coupled oscillators. Based on two classical oscillator models, i.e., the Poincaré model and the Stuart–Landau model, the emergence of explosive oscillation death is independent of the frequency distributions. Our findings indicate that the first-order phase transitions can be induced by the frequency-amplitude correlation for the first time. Therefore, it provides a novel perspective to understand explosive phenomena in coupled oscillators.